The Impact of Agricultural Extension for Improved Management Practices: An Evaluation of the Uruguayan Livestock Program - Alessandro Maffioli; Conner Muffally (Inter-American Development Bank (IDB), 2014)
Management is an important input into agricultural production, as it a determinant of the uptake and proper implementation of productive technologies and practices. While there is a large literature on evaluations of extension programs meant to improve management practices in agricultural development, there is no consensus on the extension modalities that are most effective. This paper adds to the literature on extension interventions by evaluating the Uruguayan Livestock Program (ULP), a publicly funded, privately delivered extension program designed to improve management practices among cattle breeders. Using an eight year panel constructed by combining data from the Uruguayan livestock traceability system with a registry of ULP participants, we place bounds on the impact of the program on production and sales of calves by ULP beneficiaries using inverse probability weights estimated using propensity scores for selection into the ULP and selection into the dataset. Results show that the ULP increased calf production by between 11.36 and 15.3 calves on average in 2009 and 2010 and increased calf sales minus purchases by 4.35 on average over the same time span. Internal rates of return suggest these are moderately sized economic impacts. We examine the aspects of the ULP's design that might account for its positive but modest effects.
hdl:11319/4776
Keywords: M11; O13; O22; Q12; Q16; 330; agricultural extension; agricultural production; impact evaluation; livestock